Vacuum frying foods: products, process and optimization - Diamante, L. M. (2016)
Vacuum frying is a reasonably new technology which uses lower pressure and temperature rather than atmospheric deep-fat frying to improve the quality attributes of food products. This work reviewed published research papers on vacuum fried foods from 2012 to the present, including some papers not covered by two recent reviews. The review covered the vacuum frying system, the vacuum frying process, product, process and optimization, oil uptake, changes in the oil during vacuum frying, and packaging and shelf life of vacuum fried foods. The vacuum fried products processed comprised of fruits, vegetables, fish and wheat-based snacks. Some of the studies recommended optimized conditions for a number of products including apple, apricot, carrot, grass carp, gold and green kiwifruits, mushrooms, potato and shallots. Generally, the higher the frying temperature the shorter the frying time. However, there was a wide range of vacuum pressures used ranging from 1.33 to 90 kPa with more than half of the processes carried out at lower than 10 kPa. Many of the products were not centrifuged after vacuum frying so would be expected to have higher oil content. For the vacuum fried products that were centrifuged, these were either carried out within the frying chamber or outside it, using speeds of 140-1000 rpm for 2-10 minutes.